Strategy in the making: Russia-NATO Relations under Strategic Competition - Luis Alexander Montero Moncada; Maria Paula Velandia García (Estudios en Seguridad y Defensa)
In this article, we examine the elements that are being developed by NATO and Russia in a strategic competition in Europe. Having analysed these elements, each sub-system, as described by the Realist Theory of International Relations, is facing major changes in today’s world politics. From Northern Europe to the Balkans and the Black Sea region, the analysis focuses on areas of tension that could potentially become problematic for the interaction between the two actors. Besides, the Baltic region is explained further due to its continuous activity regarding either hybrid or tradition war tactics. Finally, we draw a parallel between NATO, the EU and the USA as main actors in European Security and how the latter has been changing drastically since Donald Trump took office. We conclude by analysing potential risks, scenarios and conflicts between NATO and Russia in short range projections.